Care and dialog: interactions and integrality in the daily life of neonatal assistance - Patrícia Pinto Braga; Roseni Rosângela de Sena (Rev Rene)
This is a study of approximation with the daily life of care to new born children at risk. It proposes to learn how the interpersonal communication process interferes in the practice of integrality in the care of new born children in the Neonatal Intensive Therapy Unity. An option was made to use a qualitative approach, oriented by theoretical-methodological references. Participative observation and focal groups with professional were used as a strategy of apprehension of reality. This work was developed at a maternity in the city of Belo Horizonte, Minas Gerais, Brazil. The data analysis reveals that the power relations in the daily life of dialogical care need to be seen as permanent negotiation possibilities and possibilities of changes. Communication was identified as the strategy to construct integral actions. Therefore, it is necessary to create spaces to make it to happen, resulting in the care centered in the new born children and their family.